Extending UML templates towards computability - Farinha, J.; Ramos, P. (Proceedings of the 3rd International Conference on Model-Driven Engineering and Software Development, 2015)
UML templates allow the specification of generic model elements that can be reproduced in domain models by means of the Bind relationship. Binding to a template encompasses the substitution of that template’s parameters by compatible domain elements. The requirement of compatibility, however, is checked over by UML in a very permissive way. As a consequence, binding to a template can result in badly-formed models and non-computable expressions. Such option in the design of UML was certainly intentional and meant to allow for richer semantics for the Bind relationship, as the specialization of the concept is advised at several points of the standard. This paper proposes one such specialization. One that guarantees well-formedness and computability for elements bound to a template. This is achieved by introducing the concept of Functional Conformance, which is imposed between every template’s parameter and its application domain substitute. Functional conformance is defined in terms of well-formedness rules, expressed as OCL constraints on top of OMG’s UML metamodel.